Crystallization Kinetics of Commercial PLA Filament - Adam Balazs (Communications - Scientific letters of the University of Zilina, 2017)
The Poly-Lactic Acid (PLA), the often used material for 3D printing and the rapid prototyping is very important in development process in automotive industry, as well. The commercial PLA filament was chosen and isothermal melt-crystallization and melting behavior was investigated by the DSC (differential scanning calorimetry). The PLA is a semi - crystalline biopolymer but the crystallization process is slow and sensitive to the changing of the cooling rate. Avrami equation was applied to analyze the crystallization. Arrhenius equation was used to calculate the activation energy and the equilibrium melting temperature was determined by the Hoffman-Weeks linear method. These results are the basis for further experiments.